2016
DOI: 10.1002/2016gl068498
|View full text |Cite
|
Sign up to set email alerts
|

Does the Madden‐Julian Oscillation modulate stratospheric gravity waves?

Abstract: The circulation of the stratosphere is strongly influenced by the fluxes of gravity waves propagating from tropospheric sources. In the tropics, these gravity waves are primarily generated by convection. The Madden‐Julian Oscillation (MJO) dominates the intraseasonal variability of this convection. However, the influence of the MJO on the variability of stratospheric gravity waves is largely unknown. Here we examine gravity wave potential energy at 26 km and the upper tropospheric zonal wind anomaly of the MJO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Intraseasonal variability in the equatorial mesosphere has also been reported by Liebermann (1998), Pancheva et al (2003), Sridharan et al (2007), and Guharay et al (2012). Since the ISO seen in the MLT region has a similar period to the MJO, a possible relation between these ISO variations has been suggested (Eckermann et al, 1997;Moss et al, 2016;Yang et al, 2017). As suggested by Garcia (2000), Isoda et al (2004), and Kumar et al (2007), MJO-related convective anomalies are considered to be related to the ISO variabilities in nonmigrating tides.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Intraseasonal variability in the equatorial mesosphere has also been reported by Liebermann (1998), Pancheva et al (2003), Sridharan et al (2007), and Guharay et al (2012). Since the ISO seen in the MLT region has a similar period to the MJO, a possible relation between these ISO variations has been suggested (Eckermann et al, 1997;Moss et al, 2016;Yang et al, 2017). As suggested by Garcia (2000), Isoda et al (2004), and Kumar et al (2007), MJO-related convective anomalies are considered to be related to the ISO variabilities in nonmigrating tides.…”
Section: Introductionmentioning
confidence: 72%
“…Eckermann and Vincent (1994) first reported ISO of the zonal wind in the equatorial MLT from medium-frequency radar observations. Since the ISO seen in the MLT region has a similar period to the MJO, a possible relation between these ISO variations has been suggested (Eckermann et al, 1997;Moss et al, 2016;Yang et al, 2017). Since the ISO seen in the MLT region has a similar period to the MJO, a possible relation between these ISO variations has been suggested (Eckermann et al, 1997;Moss et al, 2016;Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Madden-Julian oscillation (MJO) is the dominant mode of the tropospheric intraseasonal oscillation (ISO) and is characterized by repeated eastward-propagating deep convection and coupled circulation (Madden & Julian, 1971, 1972, with a period of~30-80 days (e.g., Zhang, 2005). As suggested in previous studies, MJO events interact with tropospheric phenomena such as El Niño-Southern Oscillation (ENSO) and monsoons Waliser et al, 2003) and affect anomalous planetary waves (PWs) and gravity wave activities (Gill, 1980;Moss et al, 2016;Schwartz et al, 2008;Zagar & Franzke, 2015). MJO-induced adiabatic heating in the tropics could excite PWs in the middle and high latitudes (Ferranti et al, 1990;Seo & Son, 2012), which would affect the variations in the Northern Annual Mode (Cassou, 2008;Lin et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Eckermann et al (1997) reported MJO-like oscillations in the equatorial MLT winds and suggested that they are modulated by GWs and tides excited by tropical convection which has MJO signals. More recently, Moss et al (2016) used observations from the Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) satellite and found a strong anticorrelation between the GW potential energy at 26 km and the MJO eastward wind anomaly. They suggested that this anticorrelation results from the filtering of GWs by the MJO winds.…”
Section: Introductionmentioning
confidence: 99%